The Development of a Sustainability Literacy Instrument on Alternative Energy Contexts as an Effort to Promote Climate Change Mitigation - Suana, Wayan; Aini, Umi Nur; Ertikanto, Chandra; Distrik, I Wayan (Unnes Science Education Journal, 2024)
Research on sustainability literacy among high school students, particularly in the context of energy use and alternative energy, is limited, especially in developing countries like Indonesia. This study aims to fill this gap by developing and validating an instrument to assess sustainability literacy focused on alternative energy. Using the 4D model (define, design, develop, disseminate), the instrument was evaluated by two university lecturers and one high school teacher, achieving a validity score of 84.8%, classified as very good. A readability test with 10 students yielded a score of 91.8%, indicating easy comprehension. The instrument was tested on 70 students, and Rasch analysis, performed using Ministep software, revealed a strong fit with infit and outfit Mean Square (MNSQ) values close to 1.00 and Z-standard (ZSTD) values near 0.00. Reliability scores were 0.82 for knowledge, 0.84 for abilities, and 0.80 for mindset, indicating the instrument's dependability. Overall item reliability exceeded 0.90, confirming the tool's consistency. This validated instrument is a practical and reliable tool for assessing sustainability literacy in high school students, particularly in alternative energy education, and can support educational efforts aimed at mitigating climate change through enhanced understanding of sustainable energy solutions.